A new gall crab species (Brachyura, Cryptochiridae) associated with the free-living coral Trachyphyllia geoffroyi (Scleractinia, Merulinidae) - Sancia E.T. van der Meij (ZooKeys, 2015)
A new species of gall crab is described from the free-living stony coral Trachyphyllia geoffroyi. Specimens were collected during field work in Lembeh Strait (Indonesia) and off Kudat (Malaysian Borneo). This new species, here named Lithoscaptus semperi sp. n., is the ninth species assigned to the genus. It can be separated from its congeners by not having the internal orbital angle extending beyond the external orbital angle, and by the stout female P2 merus with prominent distomesial projection. In addition, the carapace surface appears smooth, despite having small tubercles on the anterior half, and is without noticeable spines, other than those on the frontal margin. The distinctive carapace pattern in life is a diagnostic character in male specimens.